Identifikasi Patahan Menggunakan Analisis Data Deformasi Tanah di Tapak RDE Serpong - Suntoko, Hadi; Sriyana (BRIN Publishing, 2017)
Experimental Power Reactor (EPR) site is located in Serpong and it has a distance of ± 67 km from the Cimandiri active fault. Result of EPR site evaluation show that it is feasible and safe from the active fault. However, it is necessary to monitor the rock deformation by using Global Positioning System(GPS) tool. The goal is to obtain precise coordinates through GPS data to identify the presence of active fault activity and its impact on the site. The monitoring is using six measuring points configuration mounted crossing the southeast-northwest suppose fault line direction. The research method is using coordinate data collection from BATAN GPS periodic station and BIG GPS continuous station in radius 25 km. Data processing is using Bernese Version 5.2 Software, proceed radially from station 1 as reference point and then continued by data interpretation. The Analysis result shows that the fault/tectonic condition near EPR site is in the range of 0.05 microstrain which is an area with stable tectonic condition.